Indication of endovascular treatment of type B aortic dissection - Literature review - Duarte,João Jackson (2014)
Aortic dissection is a cardiovascular event of high mortality if not early diagnosed and properly treated. In Stanford type A aortic dissection, there is the involvement of the ascending aorta, whereas in type B the ascending aorta is not affected. The treatment of type A aortic dissection is mainly surgical. The hospital mortality of type B aortic dissection surgical treatment is approximately 20%, while medical therapy is 10%. However, half the patients who are discharged from hospital after medical treatment, progress to aortic complications in the following years, and the mortality in three to five years may reach 25-50%. In addition, the surgical treatment of aortic complications after medical treatment, has also a significant mortality. This way, the endovascular treatment comes up as an interesting alternative of a less invasive treatment for this disease. They presented a mortality rate lower than 10% with more than 80% success rate of occlusion and thrombosis of the false lumen. The INSTEAD TRIAL, which randomized patients with uncomplicated type B aortic dissection for optimal medical therapy and endovascular treatment in addition to optimal medical therapy, showed that after three years of follow up, patients who underwent endovascular treatment had lower mortality and aorta-related complications. Therefore, there is a current tendency to recommend the endovascular treatment as a standard for the treatment of type B aortic dissection